Integrating phylogeographic and phenotypic evidence to delimit deep evolutionary lineages in the Dryophytes japonicus species complex, with an assessment of their conservation needs - Amaël Borzée; Yikweon Jang; Siti N. Othman; Jordy Groffen; Irina V. Maslova; Zoljargal Purevdorj; Kiyomi Yasumiba; Tomohiko Shimada; Yoonjung Yi; Natalya Alekseevna Schepina; Desiree Andersen; Yoonhyuk Bae; et al. (Herpetozoa)
Proper taxonomic and phylogeographic frameworks are a prerequisite in evolutionary, ecological, and conservation research, but many species still lack adequate assessments. Earlier studies on the northeast Asian treefrog, Dryophytes japonicus, identified a deep Mio-Pliocene diversification; however, phenotypic assessments were lacking, and the taxonomic identity of the identified clades is under debate. In this study, we assessed the genetic, genomic, morphological, and acoustic diversity and differentiation within the D. japonicus complex to propose taxonomic arrangements and assess taxon-specific threats for each defined clade. Analyses of four mtDNA genes and 42.8 kb nuclear loci obtained by RAD-sequencing (RAD-seq) confirmed two distinct species-level clades that diverged ~6 Mya, one provisionally assigned to D. japonicus in southern Japan and mainland Asia and the other unnamed (D. cf. japonicus) in northern Japan and adjacent Russian islands. According to the mitochondrial data, each species is further divided into two subclades of Pleistocene age that display differences in morphological and call properties that may represent candidate subspecies: D. j. japonicus in southwestern Japan and D. j. stepheni on the Asian mainland and two unnamed lineages in Central and Northern Japan for D. cf. japonicus. Phenotypic differentiation between populations was only partly linked to their phylogenetic relationships. Finally, despite the relatively narrow ranges of many lineages, none crosses the threshold to be currently listed as threatened. The conservation of the diversity of the D. japonicus complex will necessarily require proper population monitoring and additional investigations to evaluate whether the unnamed delimited lineages merit taxonomic descriptions.